OANA-RAMONA ILOVAN & IWONA MARKUSZEWSKA (Eds.). 2022. Preserving and Constructing Place Attachment in Europe. Cham: Springer, 369 p. (Annals of the University of Bucharest. Geography Series, 2024)
Despite its variety, the book is structured in four sections, each one dealing with a specific aspect of place attachment.